Akuntabilitas Pengelolaan Alokasi Dana Desa (ADD) Desa Lumindai Kecamatan Barangin Kota Sawahlunto Tahun 2019 - Suardi, Suardi; Nazirwan, Nazirwan; Fitriani, Fitriani (LPPM Universitas Ekasakti, 2021)
Research is done at Lumindai's Village, Goods district, Sawahlunto's city. Problem identification: Allocation Management accountability Lents Fund Village On Silvan Lumindai has pointed out administration that corresponds to prevailing rule, lack for and administration incompleteness make Allocation Management accountability Lents Fund imperfect Village and constraining deep Allocation channelizing proffering Lents Fund Village. To the effect, this research to know how is accountability Allocation management Lents Fund Lumindai's Village and it's therewith constraint effort that is done in settle that constraint. Akuntabilitas's conclusion Allocation Management Lents Fund Lumindai's Village was good, really and according to operation default procedures (SOUP), but there is constraint sort as reducing its tech guidance and coordination among institute. An effort that needs to be done to settle that constraint by follows bimtek and interlaces good coordination institution squire concerning.